Novel Multifunctional Spherosilicate-Based Coupling Agents for Improved Bond Strength and Quality in Restorative Dentistry - Raszewski, Zbigniew; Brząkalski, Dariusz; Jałbrzykowski, Marek; Pakuła, Daria; Frydrych, Miłosz; Przekop, Robert E (Materials (Basel, Switzerland), 2022)
The aim of this study was to investigate the restorative connections of composite materials after fracture, under controlled conditions of treating the materials with novel, spherosilicate-based (SS) primers bearing both methacryl (MA) and trimethoxysilyl (TMOS) groups. The chemistry of methacrylate group insertion and reactive groups hydrolysis has been studied with the aid of 1H NMR (Nuclear Magnetic Resonance) spectroscopy. The light-cured resin composites were repaired by activating the connection site with the obtained primers and, for comparison, a silane (methacryloxypropyltrimethoxysilane, MATMOS) as a conventional coupling agent bearing the same reactive groups. The resistance of such a joint was tested in a three-point bending test after 24 h and 28 days period of sample conditioning. The effect of bond application was also studied, showing that spherosilicate-based primers may be used more effectively than MATMOS for two-step (primer-composite) restorative process, while for silane, the three-step process with bond application is crucial for satisfactory joint quality. The joint failure mode was determined by microscopic analysis and it was found that SS-4MA-4TMOS and SS-2MA-6TMOS application resulted in mostly composite, and not joint, failure. After 28 days of conditioning, the flexural strength of the joint repaired with SS-4MA-4TMOS was at 94% of the neat, solid material under the same procedure. However, the strength of the neat composite was observed to decline during the conditioning process by ~30%. The joint behavior was explained on the basis of the gradual hydrolysis effect (the greatest decrease being observed for silane).
Keywords: SSQ; adhesive; stomatology; POSS; oral medicine; light curable; cage siloxane